Modeling mechanisms for preventing social ostracism in the student environment - Assylbekova, Marziya; Shaikhymuratova, Indira; Baіmenova, Botagoz; Zhubakova, Saule; Temirov, Kuanysh (International Journal of Innovative Research and Scientific Studies, 2025)
Social ostracism is a critical issue in educational settings, adversely affecting students’ motivation, psychological well-being, and social integration. This study aims to identify effective mechanisms for preventing social ostracism among university students and assess the impact of the "SOCI-PROGRESS" methodology, a structured intervention designed to enhance student interactions and foster inclusivity within the academic environment. The study employed a mixed-method research approach, integrating both quantitative and qualitative methods. The Ostracism Experience Scale for Adolescents (OES-A) Gilman [1] was used to measure the prevalence and severity of social exclusion among 161 students from the Faculty of Journalism and Social Sciences at Madina and Gumilyov [2] Eurasian National University. Data were collected through questionnaires, direct observations, and expert interviews with faculty members. The study revealed statistically significant reductions in key indicators of social ostracism, including ignoring (-17.6%), exclusion (-20.8%), and rejection (-18.2%). The "SOCI-PROGRESS" methodology, which included mentorship programs, group discussions, and social integration activities, contributed to enhanced student participation, an increased sense of belonging, and improved interpersonal relationships. The findings confirm that a systematic and structured approach to addressing social ostracism can significantly enhance social integration among students. Implementing targeted mentorship initiatives, interactive educational programs, and institutional support systems plays a crucial role in mitigating the negative effects of exclusion and fostering an inclusive academic environment. The study offers practical recommendations for educational institutions seeking to reduce social isolation. These include developing peer mentorship programs, implementing student support networks, integrating social-emotional learning modules into curricula, and enhancing faculty involvement in student well-being initiatives.